Design-for-reliability methodology for lead-free solder joints - Low, Tse Hoong (2008)
In this project, a Design-For-Reliability (DFR) methodology was developed for solder joints. This methodology consists of three parts, (1) experimental methods for reliability test, (2) Finite Element Analysis (FEA): Modeling and Simulation and (3) Fatigue Life Prediction Analysis. This methodology aims to reduce the time taken to understand and improve the reliability and performance of electronic assemblies with lead-free solder joints.